Never touch a polar bear! - Rosie Greening (Hertfordshire; Make Believe Ideas Ltd., 2019)
"You must never touch a polar bear--unless it's in this book! This festive touch-and-feel board book is [meant] for children of all ages and fits perfectly into tiny hands. Kids will love reading the silly rhymes that warn [of] the dangers of touching the wintery animals--and then ignoring the advice!"
Keywords: Board books